Mitigation strategies to fight the COVID-19 pandemic - present, future and beyond - Zainul Abideen, Ahmed; Fazeeda, Mohamad; Mohd Rohaizat, Hassan (Emerald Group Publishing Ltd., 2020)
The latest novel coronavirus disease 2019 (COVID-19) pandemic continues to have a significant social and financial impact globally. It is very essential to study, categorize and systematize published research on mitigation strategies adopted during previous pandemic scenario that could provide an insight into improving the current crisis. The goal of this paper is to systematize and identify gaps in previous research and suggest potential recommendations as a conceptual framework from a strategic point of view. Design/methodology/approach: A systematic review of Scopus and Web of Science (WoS) core collection databases was performed based on strict keyword search selections followed by a bibliometric meta-analysis of the final dataset. Findings: This study indicated that the traditional mitigation techniques adopted during past pandemics are in place but are not capable of managing the transmission capability and virulence of COVID-19. There is a greater need for rethinking and re-engineering short and long-term approaches to prevent, control and contain the current pandemic situation. Practical implications: Integrating various mitigation approaches shall assist in flattening the pandemic curve and help in the long run. Originality/value: Articles, conference proceedings, books, book chapters and other references from two extensive databases (Scopus and WoS) were purposively considered for this study. The search was confined to the selected keywords outlined in the methodology section of this paper.